Prevalence and Risk Factors Associated with Neisseria gonorrhoeae among Individuals in Obigbo, Rivers State - Olotu, Olayemi Favour; Kenneth, Imarenezor Edobor Peter (Darul Yasin Al Sys, 2025)
Neisseria gonorrhoeae is a major public health concern due to potential for severe complication of infertility and pelvic inflammatory disease. This study assessed the prevalence and risk factors associated with Neisseria gonorrhoeae infection among youths in Obigbo, Rivers State, Nigeria. Using a cross-sectional design, 288 participants aged 16-35 years comprises of 105 males and 183 females were study to evaluate infection prevalence, awareness, and sexual health behaviors influencing transmission. Data collection was done using a structured questionnaire capturing demographic information, awareness levels, and risk-related behaviors, alongside rapid diagnostic testing for N. gonorrhoeae. Descriptive statistics and chi-square tests were used to analyze relationships between demographic variables and infection risk. Findings indicated a prevalence of 8 (2.78%), with a higher rate observed among males 5 (4.76%) than females 3 (1.64%). The higher prevalence among males and those within younger age brackets suggests behavioral patterns and risk perceptions that could be addressed through targeted public health interventions. Additionally, the study emphasizes a significant gap in awareness of Neisseria gonorrhoeae, underlining the need for improved health education focused on sexually transmitted infection (STI) prevention. Infection was more frequent among individuals aged 16-20 years with males having high incidences and 21-25 years with females having the highest incidences, highlighting age-specific vulnerabilities. The risk factors included inconsistent condom use, limited awareness of N. gonorrhoeae, and a history of multiple sexual partners. Gender and educational background were significantly associated with awareness and preventive behaviors. Generally, the findings underscore the necessity of accessible sexual health services, community-based education programs, and socioeconomic support systems to address not only STI risks but also broader health disparities. Targeted interventions that consider both individual behaviors and social determinants of health may be effective in reducing the prevalence of Neisseria gonorrhoeae and improving the sexual health of youths in Obigbo, ultimately contributing to healthier and more informed communities in Rivers State.